2023
DOI: 10.57125/fed.2023.25.03.10
|View full text |Cite
|
Sign up to set email alerts
|

Formation of digital competence in higher education students as a basis for the transformation of education of the future

Abstract: The education informatization together with the rapid spread of computer technology actualizes the need for thorough information training of future teachers. The purpose of the study is to analyze the applicants for higher education digital competence based on the features of modern education. In the work were used general scientific methods: analysis, synthesis, deduction. By means of prediction method, further opportunities for the development and improvement of the digital competence of students are charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…However, the consistency, coherence, and continuity of the preparation for the digital transformation are what ensure the efficacy of the development of the digitalization of education. Digital proficiency is also a requirement for the development of the teachers of the future [59]. It was reported that the ideal case for case-based education should be relevant, realistic, engaging, challenging, enlightening, enjoyable, and based on a real-world professional context [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, the consistency, coherence, and continuity of the preparation for the digital transformation are what ensure the efficacy of the development of the digitalization of education. Digital proficiency is also a requirement for the development of the teachers of the future [59]. It was reported that the ideal case for case-based education should be relevant, realistic, engaging, challenging, enlightening, enjoyable, and based on a real-world professional context [22].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Bezlutska et al (2021) indicates that modern professional training of future specialists should be based on the development of various competencies, including managerial ones. At the same time, Ostanina et al (2023) focused their study on the peculiarities of forming digital competence for modern teachers. The authors note that an important way to improve it is the participation of teachers themselves in special courses and webinars (p. 132).…”
Section: Discussionmentioning
confidence: 99%
“…As modernas tecnologias digitais são uma ferramenta eficaz para o desenvolvimento de uma instituição educacional e do processo educacional, enquanto a variedade de plataformas, recursos e ferramentas digitais inovadoras permite implementar o processo educacional remotamente, levando em consideração as capacidades individuais de cada participante no processo educativo. As ferramentas digitais atuais e as tecnologias de informação e comunicação facilitam a troca rápida de informações, os últimos desenvolvimentos científicos, certos conhecimentos e experiências, e permitem o desenvolvimento efetivo da educação a distância (NADRLJANSKI; STEVO; MILICA, 2019).Pesquisadores comprovam que a organização do ensino a distância cria muitas oportunidades ilimitadas de aprendizado, o que geralmente melhora a educação de todos(OSTANINA et al, 2023). Independentemente do local de residência, os alunos podemNovas práticas da formação em design de trabalhadores científicos e pedagógicos: Tecnologias digitais no contexto da integração do ensino a distância Política e Gestão Educacional, Araraquara, v. 27, n. esp.…”
unclassified